2018
DOI: 10.1002/cctc.201701763
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Aspects of Acrylic Acid Formation from CO2–Ethylene Coupling over Palladium‐ and Nickel‐based Catalysts

Abstract: The detailed mechanism of catalytic conversion of CO2 and ethylene to acrylic acid has been investigated through DFT and DLPNO‐CCSD(T) calculations. Four bidentate ligands, dmpe (1,2‐bis(dimethylphosphino)ethane), dcpe (1,2‐bis(dicyclohexylphosphino)ethane), dtbpe (1,2‐bis(di‐tert‐butylphosphino)ethane), and tmeda (tetramethylethylenediamine) were systematically studied to understand the different catalytic behavior of the Pd‐based catalyst and the well‐known Ni‐based catalyst. The energy barrier of Pd‐/Ni‐cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 74 publications
1
18
0
Order By: Relevance
“…However, the Pd(dcpe)/E system was apparently less hindered in routes 7→6 and 8→6 than the Ni(dcpe)/E system. In our previous study, we also found that the Pd center was more active than the Ni center during the β‐H elimination when bulky ligand was selected, while the Ni‐catalyst showed better performance with small ligands . Here during the base‐assisted β‐H elimination, the nickel center was also more efficient than the palladium center under less hindered environment, while the palladium center surpassed the nickel center in crowded circumstance.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…However, the Pd(dcpe)/E system was apparently less hindered in routes 7→6 and 8→6 than the Ni(dcpe)/E system. In our previous study, we also found that the Pd center was more active than the Ni center during the β‐H elimination when bulky ligand was selected, while the Ni‐catalyst showed better performance with small ligands . Here during the base‐assisted β‐H elimination, the nickel center was also more efficient than the palladium center under less hindered environment, while the palladium center surpassed the nickel center in crowded circumstance.…”
Section: Resultsmentioning
confidence: 86%
“…So the purpose and primary function of the base is to eliminate the β‐H to produce acrylate, and it does not play an important role in the metallalactone formation according to former reports ,. In our last publication, the detailed C−C coupling mechanism has already been thoroughly studied . Based on the current aim to clarify the base‐assisted acrylate formation mechanism in both the Ni‐ and Pd‐catalyzed systems, hereby, we started the investigation with the metallalactone rather than the M−C 2 H 4 complex.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations